The role of cultural friction in the sociocultural integration micro-mechanisms in cross-border mergers and acquisitions - Durand, Muriel; Díaz-Pichardo, René (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2025)
This research explores the sociocultural micro-mechanisms driving the relationship between post-merger identification and organizational citizenship behavior which has been reiteratively observed but not explained in the mergers-and-acquisitions literature. Adopting a multi-paradigmatic research approach and social identity theory, we introduce interpersonal trust and cultural friction as a microfounded variable to address this research gap. Structural equation modeling on survey data from managers having experienced at least one cross-border merger and acquisition (CBM&A) offers evidence of a full mediation effect of interpersonal trust in this well-established relationship. Counterintuitively, cultural friction shows positive impacts. This study contributes to the field of CBM&As by demonstrating the usefulness of cultural friction as a microfounded variable in explaining identity formation and work-related attitudinal outcomes.